Penggunaan Media Digital Pembelajaran Sejarah dalam Masa Pandemi Covid-19 di SMA An- Nizam - Andyoda Siregar; Pulung Sumantri; Hadiani Fitri; Latifah Hanum (Keguruan, 2023)
The execution of schooling ought to have the option to synergize in different circumstances. In any event, when hit by the Coronavirus pandemic, teachers and understudies are expected to keep battling so that learning exercises can run well, however with negligible gamble of contamination. Thusly, during the pandemic the growing experience was coordinated towards the utilization of online media. Through this exploration, it is trusted that we can figure out how online media is utilized in learning history in the city of Medan. This exploration was led utilizing subjective examination techniques, while the sort of exploration utilized was distinct subjective. In the information assortment process, information sources are resolved purposively and compounding. Information assortment strategies were done utilizing perception, meetings and documentation. Moreover, the information that has been gathered is dissected by information decrease, information show, and check. The consequences of the examination show that the applications that are frequently involved by AN-Nizam Secondary School history subject educators in web based learning are WhatsApp, Google Study hall, Google Meet, Zoom Meeting, and Learning The board Framework (LMS). The web based educational experience is done utilizing general elements contained in the application, in particular sending messages, sharing material in document structure, like Microsoft PowerPoint (PPT), learning modules, and recordings, as well as through video gathering. The different hindrances confronted both connected with the utilization of innovation, educator qualities and understudy attributes can possibly prompt retrogression in web based learning.